2006
DOI: 10.2466/pr0.98.3.625-626
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Boredom Proneness

Abstract: To identify sex differences in boredom proneness, 146 undergraduates (66 men and 80 women) were asked to complete the Boredom Proneness Scale. An independent groups t test indicated a statistically significant mean difference in boredom proneness as men scored significantly higher than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
2
2
1
Order By: Relevance
“…This is consistent with other studies that have reported associations between hypersexual behavior and boredom (Chaney & Blalock, 2006). Some research suggests that men experience greater boredom proneness than women (McIntosh, 2006), possibly making boredom susceptibility a predisposing risk factor for men who become hypersexual to compensate for what they perceive to be an impoverished environment that fails to stimulate them.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies that have reported associations between hypersexual behavior and boredom (Chaney & Blalock, 2006). Some research suggests that men experience greater boredom proneness than women (McIntosh, 2006), possibly making boredom susceptibility a predisposing risk factor for men who become hypersexual to compensate for what they perceive to be an impoverished environment that fails to stimulate them.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Purpose in Life test scores and Boredom Proneness Scale scores were not significantly different for women and men (t,,, = -20, ns; t,,, = 3 5 , ns, respectively). This finding contrasts with those of several studies in which significant differences between men and women in boredom proneness were obtained (Tolor, 1989;Vodanovich & Kass, 1990b;Sundberg, Latkin, Farmer, & Saoud, 1991;Watt & Vodanovich, 1992a;Polly, Vodanovich, Watt, & Blanchard, 1993;McIntosh, 2006). With regard to sex differences in meaning in life, some studies have found that men report higher purpose in life (Crumbaugh, 1968), whereas others reported no differences between men and women (Meier & Edwards, 1974).…”
contrasting
confidence: 78%
“…The exploration of age and gender differences confirmed previous results concerning the negative association between age and PSNSU (e.g., [ 57 ]), the fact that being women positively predicted PSNSU, negative emotional reactivity (e.g., [ 55 ]) and FoMO, whereas being men positively predicted boredom proneness (e.g., [ 56 ]). However, when we explored potential differences in the structural model across men and women, the model was found to be independent of gender.…”
Section: Discussionsupporting
confidence: 85%
“…All the direct paths toward PSNSU would be tested. Age and gender would be considered as control variables as previous studies have shown that women report higher negative emotional reactivity (e.g., [ 55 ]) and less boredom proneness than men (e.g., [ 56 ]) and women and younger people report higher levels of PSNSU (e.g., [ 57 ]).…”
Section: Introductionmentioning
confidence: 99%